Work-Integrated Learning in the 21st Century : Global Perspectives on the Future. - Bowen, Tracey (Emerald Publishing Limited, 2017)
This book explores new questions about the state of work and work readiness for new university and college graduates in the context of work-integrated learning in the 21st century and the role of higher education in preparing students for the challenges of global economic shifts in the labour market.
The Mobile Technology Capacity Building Framework for WPL.
Keywords: Education, Cooperative -- 21st century.; Generation Y.; 2000-2099; elektronické knihy; electronic books